2020
DOI: 10.1177/1203475420972349
|View full text |Cite
|
Sign up to set email alerts
|

Gliptin-Induced Bullous Pemphigoid: Canadian Case Series of 10 Patients

Abstract: Background Bullous pemphigoid (BP) is a chronic immune-mediated vesiculobullous disorder. Recently, several reports have described dipeptidyl peptidase-4 inhibitors, also known as gliptins, as causative agents for drug-induced BP. Objective To report and describe clinical and histologic characteristics of 10 cases of gliptin-induced BP. Results We identified 10 patients with gliptin-induced BP. Nine were secondary to linagliptin, and 1 case was attributed to sitagliptin. All patients showed significant improve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…1,8 Recent case reports have described the development of bullous pemphigoid after initiation of dipeptidyl peptidase 4 inhibitors, such as sitagliptin and saxagliptin, in patients with diabetes, with improvement after the gliptin medication was discontinued. 9 Treatment of bullosis diabeticorum involves gentle wound care and prevention of infection. Because bullae on the feet and lower legs can limit mobility and may be associated with an increased risk of unintentional rupture, potentially resulting in large areas of denuded skin, a sterile needle can be used to aspirate large bullae.…”
Section: Discussionmentioning
confidence: 99%
“…1,8 Recent case reports have described the development of bullous pemphigoid after initiation of dipeptidyl peptidase 4 inhibitors, such as sitagliptin and saxagliptin, in patients with diabetes, with improvement after the gliptin medication was discontinued. 9 Treatment of bullosis diabeticorum involves gentle wound care and prevention of infection. Because bullae on the feet and lower legs can limit mobility and may be associated with an increased risk of unintentional rupture, potentially resulting in large areas of denuded skin, a sterile needle can be used to aspirate large bullae.…”
Section: Discussionmentioning
confidence: 99%
“…Some previous studies have approved complete remission after rapid discontinuation of drug with a different median time from 10 to 35 days, while others have seen no major change in remission between the group who continued gliptins and the group with discontinuation. However, it is generally suggested that ceasing the drug would be effective in complete remission because, based on a study, ongoing drug administration and long exposure might lead to neoepitope formation and a more complicated disease cycle [ 1 , 4 , 5 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Bullous pemphigoid (BP) is the most common acquired autoantibody blistering disease that is idiopathic and has shown a great tendency to develop in older adults [ 1 , 2 , 3 , 4 ]. The characteristic of the disease is that it mainly affects the trunk and the extremities, which can appear as several pruritic tense bullae and erythematous plaque [ 5 ]. The increasing number of BP cases is shown to be related to the increasing rate of senility, stimulated by different drugs like antibiotics and antidiabetic agents, and the ability of better diagnosis as a result of more attention paid to rare types of disease [ 1 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Pemphigoid reactions are seen to occur most frequently, with 76 of the cases attributed to this adverse event [14]. Cutaneous reactions discussed in the literature fall into the subcategories of immunologic CADRs exanthematous (generalized skin eruption [57], maculopapular eruption [58], and DRESS syndrome [59]), blistering (pemphigoids [60][61][62][63][64][65][66][67], SJS [68], TEN [68], fixed drug eruption [69]), hypersensitivity vasculitis [68], and photosensitivity [70]…”
Section: Dpp-4 Inhibitorsmentioning
confidence: 99%
“…There is continuity between the FDA reporting system and what is found in the literature regarding DPP-4 inhibitors. Twenty-one presentations of bullous pemphigoid were found within case reports and case series, with the majority arising from the administration of vildagliptin [60][61][62][63][64][65][66][67]. Described as erythematous plaques and tense, pruritic blisters without mucosal involvement, drug-induced bullous pemphigoid presented anywhere between 2-37 months after medication initiation.…”
Section: Drug Reaction Patternsmentioning
confidence: 99%